Initial core design analysis of lead (208) ‐bismuth eutectic‐cooled reactor with radial fuel shuffling. (6th February 2021) - Widiawati, Nina; Su'ud, Zaki; Irwanto, Dwi; Permana, Sidik; Takaki, Naoyuki; Sekimoto, Hiroshi
Summary: Natural uranium is utilized in a small percentage by the Light Water Reactor (LWR) and also by the once‐through Fast Breeder Reactor. One of the reactor designs that can increase the natural uranium utilization is the MCANDLE (M odified C onstant A xial shape of N eutron flux, nuclides densities, and power shape D uring L ife of E nergy production) reactor. The scheme divides the core into several discrete regions. The modified CANDLE reactor will only need natural uranium as fuel input after reaching quasi‐equilibrium conditions. In this study, We used a core with certain Plutonium (Pu) composition in each region as a startup core. Initially, the Pu content in each region imitates that of the reactor core at the quasi‐equilibrium state. We calculated the neutronics of the initial core by the SRAC that stands for S tandard R eactor A nalysis C ode S ystem and used JENDL 4.0 as a nuclear data library. Plutonium (Pu) from LWR spent fuel was utilized as the initial reactor fuel. However, excess reactivity is more than 10%. It is because there are no other fission products. Therefore, we replace other fission products with a reduction in the volume of fuel cells. The volume reduction was adjusted to the level of burnup in each region at the quasi‐equilibrium condition. Hence, there are differences in the volume reduction ratio for each fuel cell. The method can reduce excess reactivity to 5%. The reduction of the volume of fuel cells can also reduce the amount of plutonium as the initial fuel for the reactor core. Also, the spent fuel burnup is 48% FIMA. The design could increase the utilization of natural uranium without an enrichment process. Abstract : Initial core design analysis of lead (208) ‐bismuth eutectic‐cooled reactor with radial fuel shuffling has performed. The reduction in the volume of fuel cells was proposed as a substitute for fission products. The method can reduce the amount of plutonium as the initial fuel for the reactor core and also reduce reactor excess reactivity to 5%.